Governing Arab reform: Governmentality and counter-conduct in European democracy promotion in the Arab world - Helle Malmvig (Danish Institute for International Studies (DIIS), 2012)
Since the early 1990s promoters of European democracy have sought to further political reform in the Arab world through so-called reform programmes based on notions of equality and local ownership (the ENP, the Barcelona Process, and a host of bilateral reform initiatives).European reform managers have attempted to effectively steer the conduct of local actors towards political reform. Supposedly they have done so without the use of overt power and coercion. Political reform, it is often stressed, cannot be forced from outside but must come from within. How power is involved in these initiatives which claim to work from within the freedom of local subjects has been largely left untouched. Based on a Foucauldian perspective of governmentality, this article proposes to show how European reform initiatives are indeed enmeshed in relations of power that work through liberal technologies of contractualisation and partnership. However, these relations of power are far from a one-sided relationship between a passive and suppressed Arab object and an all-powerful European subject. In a second move, the article develops the concept of counter-conduct further, showing how European reform programmes have been resisted, not by being 'against', but by using the liberal assumptions of 'invitation', 'ownership' and 'gradualism' inherent in European reform programmes to i) select entry, ii) set conditions and iii) simulate reform.
Keywords: 300; Politische Reform; Demokratisierung; EU-Politik; Arabische Staaten